Pengembangan LKPD dengan Model Pembelajaran Novick untuk Meningkatkan Motivasi Belajar - Sasongko, Dimas Femy; Putriana Ningrum, Alia; Henky Irawan, Wahyu (Edumatica : Jurnal Pendidikan Matematika, 2025)
Motivating students to understand mathematical concepts is a challenge in mathematics learning. The lack of active student engagement and less varied teaching models lead to low conceptual understanding and interest in learning. Student Worksheets are used as a medium to enhance students' participation and active involvement in learning. The Novick Learning Model is chosen because it emphasizes a constructivist approach to learning. The aim of this study is to develop students’ worksheet based on Novick learning model to increase learning motivation. Research and development model which is used following the 4D (Define, Design, Develop, dan Disseminate) on 29 students of class X Senior High School Almaarif Singosari. The validation results show that Student Worksheet has an average validity of 78.9% (Valid), while its practicality reaches 82.2% (Very Practical). The N-Gain test produces a score of 71.21% (Quite Effective). Thus, the development of Student Worksheet based on the Novick learning model is proven to be valid, practical, and quite effective in increasing students' learning motivation. This research can be further developed by applying the Novick learning model to other subjects. The development of Student Worksheets can be combined with digital media or educational technology to enhance interactivity and engagement for students.